IDENTIFICATION OF SOIL TRANSMITTED HELMINTHS EGGS IN RAW VEGETABLES SOLD AT STREETFOOD STALLS IN MAKASAR SUBDISTRICT EAST JAKARTA - febrianti febrianti; Intan Kurniawati Pramitaningrum (Mandalika Veterinary Journal, 2026)
Vegetables consumed raw, such as basil (Ocimum basilicum), cabbage (Brassica oleracea), and lettuce (Lactuca sativa), are potential sources of contamination by Soil-Transmitted Helminths (STH) eggs. Contamination of these vegetables may serve as a source of helminth infection if proper washing and processing are not carried out. This study aimed to identify the presence and types of STH eggs in raw vegetables sold at street food stalls in Makasar Subdistrict, East Jakarta. A descriptive study with a cross-sectional approach was conducted using 56 samples, consisting of 23 basil, 16 cabbage, and 17 lettuce. Examination was performed using the sedimentation method with 0.2% NaOH solution at the Microbiology Laboratory, Binawan University. Of the 56 samples examined, 1 sample (4.35%) of basil was found to be positive for STH eggs. The identified STH egg was an infertile Ascaris lumbricoides. STH eggs were only detected in basil, while all cabbage and lettuce samples were negative. The presence of STH eggs in raw vegetables indicates a potential risk of parasitic contamination in uncooked foods. Public education and awareness among food vendors regarding proper washing of vegetables before consumption are necessary to reduce the risk of intestinal helminth infections.